Capturing the mammalian Hippo: Elucidating its role in cancer. Issue 10 (7th August 2013) - Nishio, Miki; Otsubo, Kohei; Maehama, Tomohiko; Mimori, Koshi; Suzuki, Akira
<x xml:space="preserve">Abstract</x> The Hippo pathway is an evolutionarily conserved kinase cascade involved in cell growth, apoptosis, development and migration. It is also crucial for stem cell self‐renewal and the maintenance of genomic stability. In addition, this pathway has the unique capacities to sense aspects of tissue architecture, such as cell polarity and mechanical tensions imposed by the surrounding microenvironment, and to control organ size and shape. All of these properties are frequently altered in tumor cells. In this review, we summarize how dysregulation of mammalian Hippo signaling is implicated in cancer.